ETR 300 : Joran Enterprise / Mohd. Syahrul Azmi Esha ... [et al.] - Esha, Mohd. Syahrul Azmi; Kamaruzaman, Roslan; Mat Saman, Mohd. Sukry; Salleh, Mohd. Redzuan (2002)
Joran Enterprise consist four partners who are Mohd. Syahrul Azmi B. Esha as a General Manager and Administration Manager, Roslan B. Kamaruzaman as a Marketing Manager, Mohd. Sukry B. Mat Saman as an Operation Manager and Mohd. Redzuan B. Salleh as a Financial Manager. Joran Enterprise concept is" Agro-Tourism" which operates in Fishing Center and Restaurant. The services that Joran Enterprise offers to customers are freshwater fishing pool and restaurant. We also provide fishing rod for rent by customers. Beside that, we also sell fishing accessories and bait to customer. Joran Enterprise's Restaurant provides Malay Traditional food and fresh fish for grill.